Which empowerment, which Health Promotion?Conceptual convergences and divergences in preventive health practices Que empowerment, qual Promoção da Saúde?Convergências e divergências conceituais em práticas preventivas em saúde - Marcos Santos Ferreira; Luis David Castiel (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
Based on the multiple meanings, "empowerment" can be identified with either conservative or critical Health Promotion approaches. From a conservative approach, the concept is viewed as an essentially individual phenomenon, centered on the provision of information and the external transfer of power in the name of the collective good. From this approach, the relationship between "psychological" and "community" empowerment is not considered. From a critical approach, the concept is viewed as a relational phenomenon that manifests itself in the dialectic conflict of interests between individuals, groups, and social classes. From this approach, "psychological" and "community" empowerment are seen as micro and macro levels of analysis, and social transformations are the result of simultaneous changes at these levels. The use of the notion of empowerment without critical reflection or political analysis of power relations in society disseminates vague, romantic, and homogeneous views of "community". Therefore, to assume the relational nature of empowerment means to accept its interdependence with the notion of participation, without which there can be no social transformation. Thus, one should be vigilant about multiple meanings that empowerment can given in Health Promotion discourse. Os múltiplos sentidos conferidos ao empowerment podem aproximá-lo de abordagens tanto conservadoras quanto críticas de Promoção da Saúde. Em roupagem conservadora, empowerment é tomado como fenômeno essencialmente individual, baseado na provisão de informação, e como transferência externa de poder em nome do bem comum. Nessa perspectiva, não são consideradas as relações entre "empowerment psicológico" e "comunitário". Em abordagem crítica, empowerment é visto como fenômeno relacional, que só se manifesta no jogo dialético de conflitos de interesses entre sujeitos, grupos e classes sociais. Nessa perspectiva, "empowerment psicológico" e "comunitário" são tomados como níveis micro e macro de análise, e as transformações sociais como resultado de mudanças simultâneas nestes níveis. O uso da noção de empowerment sem reflexões críticas e análises políticas das relações de poder na sociedade dissemina visões vagas, românticas e homogêneas de comunidade. Portanto, assumir o caráter relacional do empowerment significa aceitar sua interdependência com a noção de participação, sem a qual não há transformação social. Sendo assim, deve-se adotar postura vigilante acerca das múltiplas formas que o empowerment pode assumir nos discursos da Promoção da Saúde.